Pasireotide (SOM230) Prevents Sulfonylurea-induced Hypoglycemia in Rats - Schmid, H. A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Persistent hypoglycemia is a serious condition that is frequently reported in patients undergoing sulfonylurea treatment, often necessitating hospitalization in the event of overdose. Somatostatin is a regulatory hormone with a broad range of physiological actions that include the inhibition of insulin and glucagon secretion, predominantly via activation of the somatostatin receptor subtypes sstr5 and sstr2, respectively. Previous studies have demonstrated that octreotide, a potent somatostatin analogue with high affinity for sstr2 and moderate affinity for sstr5, significantly increases serum glucose levels and prevents recurrence of hypoglycemic episodes in patients with sulfonylurea-induced hypoglycemia. Pasireotide (SOM230) is a multireceptor-targeted somatostatin analogue with a 39-, 30- and 5-fold higher binding affinity for sstr5, sstr1 and sstr3, respectively, and a slightly lower (0.4-fold) affinity for sstr2 compared with octreotide. This study evaluated the effects of pasireotide and octreotide in rats with glyburide-induced hypoglycemia. In fasted rats, pasireotide (10 and 30 µg/kg) prevented glyburide-induced hypoglycemia in a dose-dependent manner for up to 6 h. Qualitatively similar results were observed in non-fasted rats. However, the antihypoglycemic effect of pasireotide was stronger in non-fasted rats, resulting in transient hyperglycemia. In contrast to pasireotide, octreotide 10 µg/kg did not prevent glyburide-induced hypoglycemia in fasted and non-fasted rats, while octreotide 30 µg/kg resulted in small but significant increases in blood glucose at 3 h post-dose only. These findings suggest that pasireotide could have a more potent effect than octreotide in the management of patients with severe hypoglycemia caused by hyperinsulinemia.
Keywords: hypoglycemia; sulfonylurea; octreotide; pasireotide; hyperglycemia